The radical redemption model: terrorist beliefs and narratives - Graaf, Beatrice de (Extreme belief and behavior series, 2024)
What do convicted terrorists really believe when they say they committed their acts in the name of a higher authority? Combining oral history, social psychology, and historical research, Beatrice de Graaf explores the belief systems that underlie acts of religious terrorism. From interviews with terrorist detainees from the Netherlands, Syria, Pakistan, and Indonesia-mostly jihadists and some right-wing extremists-de Graaf reconstructs life stories of surrender, struggle, sacrifice, and redemption. She unravels the nexus between extreme beliefs and terrorist activity, presenting a grounded theory of radical redemption, in which people commit acts of violence as personal, psychological quests for significance. De Graaf's analysis examines how these beliefs developed in individual cases, and what happened when the hoped-for redemption was not fulfilled. Ultimately, by focusing on the extreme beliefs of individuals, The Radical Redemption Model offers a new understanding of the elusive and perennial connection between religion and violence, and between radical beliefs and terrorism